An evaluation of the safety and immunogenicity of MVC-COV1901: Results of an interim analysis of a phase III, parallel group, randomized, double-blind, active-controlled immunobridging study in Paraguay. Issue 1 (4th January 2023) - Torales, Julio; Cuenca-Torres, Osmar; Barrios, Laurentino; Armoa-Garcia, Luis; Estigarribia, Gladys; Sanabria, Gabriela; Lin, Meei-Yun; Antonio Estrada, Josue; Estephan, Lila; Cheng, Hao-Yuan; Chen, Charles; Janssen, Robert; et al.
Abstract: Background: Data from previous studies of the MVC-COV1901 vaccine, a subunit vaccine against SARS-CoV-2 based on the stable prefusion spike protein (S-2P) adjuvanted with CpG 1018 adjuvant and aluminum hydroxide, suggest that the vaccine is generally safe and elicits a good immune response in healthy adults and adolescents. By comparing with AZD1222, this study adds to the findings from previous trials and further evaluates the breadth of protection offered by MVC-COV1901. Methods: In this phase 3, parallel group, randomized, double-blind, active-controlled trial conducted in 2 sites in Paraguay, we assigned adults aged 18–91 years in a 1:1 ratio to receive intramuscular doses of MVC-COV1901 or AZD1222 administered as scheduled in the clinical trial. Serum samples were collected on the day of vaccination and 14 days after the second dose. Primary and secondary safety and immunogenicity endpoints were assessed. In addition, other outcomes investigated were cross-reactive immunity against the Omicron strain and the induction of IgG subclasses. Results: A total of 1, 030 participants underwent randomization. Safety data was derived from this set while primary immunogenicity data involved a per-protocol immunogenicity (PPI) subset including 225 participants. Among the participants, 58% are seropositive at baseline. When compared against AZD1222, MVC-COV1901 exhibited superiority in terms of neutralizing antibody titers and non-inferiority in terms of seroconversion rates. Reactogenicity was generally mild and no serious adverse event was attributable to MVC-COV1901. Both vaccines have a Th1-biased response predominated by the production of IgG1 and IgG3 subclasses. Omicron-neutralizing titers were 44.5 times lower compared to wildtype-neutralizing titers among seronegative individuals at baseline. This fold-reduction was 3.0 times among the seropositive. Conclusion: Safety and immunogenicity data of MVC-COV1901 from the study in Paraguay confirm previous results. The previous infection coupled with vaccination of this vaccine may offer protection against the Omicron strain though its durability is still unknown.